Forced orthodontic eruption for augmentation of soft and hard tissue prior to implant placement - Molon, Rafael Scaf de [UNESP]; Avila, Érica Dorigatti de [UNESP]; Souza, João Antonio Chaves de [UNESP]; Nogueira, Andressa Vilas Boas [UNESP]; Cirelli, Carolina Chan [UNESP]; Margonar, Rogerio; Cirelli, Joni Augusto [UNESP] (Wolters Kluwer, 2013)
Forced orthodontic eruption (FOE) is a non-surgical treatment option that allows modifying the osseous and gingival topography. The aim of this article is to present a clinical case of a FOE, which resulted in an improvement of the amount of available bone and soft-tissues for implant site development. Patient was referred for treatment of mobility and unesthetic appearance of their maxillary incisors. Clinical and radiographic examination revealed inflamed gingival tissue, horizontal and vertical tooth mobility and interproximal angular bone defects. It was chosen a multidisciplinary treatment approach using FOE, tooth extraction, and immediate implant placement to achieve better esthetic results. The use of FOE, in periodontally compromised teeth, promoted the formation of a new bone and soft-tissue in a coronal direction, without additional surgical procedures, enabling an esthetic, and functional implant-supported restoration.
Keywords: Bone remodeling; Forced eruption; Multidisciplinary treatment; Orthodontic extrusion